Effects of peripheral muscle strength asymmetries on muscle fatigability in professional soccer players - Ferioli, D.; Rampinini, E.; Martin, M.; Bosio, A.; Azzolini, M.; Maffiuletti, N. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Soccer is a high-intensity intermittent team sport, during which neuromuscular factors are heavily taxed to perform quick accelerations, decelerations, and changes of direction (COD) [1]. Inter-limb strength asymmetries have been reported to negatively affect physical performance including COD tasks across various team sports [2], however little is known about their impact on muscle fatigability during soccer specific exercises such as repeated CODs. Therefore, this study examined the effect of peripheral muscle strength asymmetries across a repeated COD task on muscle fatigability in adult professional soccer players.